The Effect of Compensation, Empowerment and Competency Toward Performance of Lecture in Wiralodra University of Indramayu - Hr, Sumardi (Universitas Malikussaleh, 2019)
The performance of Wiralodra University (UNWIR) lecturers has not been fully in line with the expectations. Achievement of lecturer performance at UNWIR is quite good category. This study aims to determine the effects resulting from compensation, empowerment and competence on the performance and compensation and empowerment on competence of UNWIR lecturers. The method used in this study is quantitative associative that 104 respondents of UNWIR lecturers are assigned. The data was collected by using performance appraisal instrument by chairman of UNWIR and lecturer response instrument relating to the compensation, empowerment and competence of UNWIR lecturer. Data processing were analyzed using path analysis by LISREL 9.30 software. The result showed that performance appraisal of lecturers of UNWIR by chairman of UNWIR is quite less / low category, response of lecturer on compensation received is sufficient, the empowerment done by UNWIR to the lecturer is enough and the competency assessment of each lecturer are respectively in the good category and overall there is a significant there is a relationship between compensation, empowerment and competence on performance and relationship between compensation and empowerment on competence.